Тема Петербурга в историософской трилогии Д.С. Мережковского “Царство зверя” - Черников, И.Н. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2009)
Д.С.Мережковский – первый из символистов, создавший в художественной прозе образ “петербургской темы” в русской литературе. Задачей предлагаемой статьи является рассмотрение особенностей изображения Петербурга как камертона повествования и “генератора смыслов” в историософской трилогии Мережковского “Царство Зверя”. Образ Петербурга во второй трилогии Мережковского порождает размышления о мессианской роли России, мысли о пограничных онтологических ситуациях. Петербург у Мережковского – модель самого мира, не сводимого к определенной географической точке. D.S.Merezhkovsky is the first of Symbolists who created in literary prose the image of the “Peterburg theme” in Russian literature. The aim of our article is to view the peculiarities of the Peterburg image as the main theme of the text and the “meaning producer” in the historiosophical trilogy of Merezhkovsky “The Reign of the Beast”. The image of Peterburg in the second trilogy of Merezhkovsky associates with the Messiah role of Russia, with ontological contradictive situations. Merezhkovsky’s Peterburg is the model of world itself, not only a geographical point.